Ocorrência de bromélias em matas ciliares: distribuição e abundância como ferramenta para avaliação de impactos antrópicos - Bernardon, Eloisa (2018)
The riparian forests are fundamental for the maintenance of biodiversity and present ecological conditions for the development of epiphytes that are indicators of environmental quality. However, these forests have suffered negative impacts related to anthropization, such as agriculture, livestock and urbanization. In this study, we intend to evaluate the distribution of Bromeliaceae in places where the riparian forest presents different dimensions in order to verify differences in composition and abundance between the sites and thus to verify its potential as indicators of environmental impact. For this purpose, 12 points were evaluated in a section of the riparian forest of the São Francisco Verdadeiro river in the municipality of Toledo - PR, 6 sites with forest width greater than 100 meters and 6 sites smaller than 100 meters. At each point, 5 quadrants containing 100 m2 (10mx10m) were determined along the river bank to the edge of the forest, registering: distance from the river, number of individuals and in the case of epiphyte species: host tree size and location forophyte. In order to verify the spatial distribution of the species, a main effects analysis (PCoA) was performed and from the number of individuals the values of the community attributes (richness, diversity and equitability) were obtained in which a Factorial ANOVA analysis was applied. A total of 399 individuals including epiphytes and terrestrial were recorded and the most abundant species were Bromelia antiacantha and Acanthostachys strobilacea. It was noted that the largest number of species is located in the first quadrant indicating preference of the species along the river's edge. In addition, the greatest number of species appeared in the fragments with more than 100 meters and most of the genera presented positive correlation in these fragments by the Analysis of Principal Coordinates (PCoA), evidencing then that the size of the fragment has influence on the abundance of Bromeliaceae and that they are indicative of biotic integrity.